Критерії правомірності інформаційної згоди пацієнта - Щирба, М.; Shchyrba, M. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається питання права пацієнта на згоду щодо медичного втручання. Вказано, що право пацієнта на добровільну згоду чітко субординується з обов’язком медичного працівника та закладу охорони здоров’я надати повну, комплексну, доступну інформацію останньому. Виділено критерії правомірності інформаційної згоди пацієнта. The article discusses the patient's right to consent for medical intervention. It is substantiated that in order to avoid violation of the right to personal inviolability and freedom and to prevent torture or inhuman treatment in health care sphere voluntary consent of the patient ought to become one of the first priority rights for interaction at the doctorpatient level. The right to consent should be understood in this way: the health and medical care authorities and relevant specialists are required to provide the patient with complete information about the future treatment or operation, including the attendant risks and inconveniences, possible side effects, as well as alternative options. The right concerns the medical workers duty and the health care institution obligation to provide patient with complete, comprehensive and accessible information. The author lays emphasis on the following patient's eligibility of the information consent criteria: the patient's right to consent; consent must be signed freely, be concrete and timely. Complete awareness of the patient and consciousness of the consent are top priority criteria.
Legitimacy Criteria of Patient's Information Consent
Keywords: згода; інформаційна згода; пацієнт; права пацієнта; критерії правомочності; consent; information consent; patient; patient rights; eligibility criteria